PENGARUH MANIPULASI SUHU KANDANG TERHADAP KADAR GLUKOSA DAN UREA DALAM DARAH PADA KAMBING BOER DAN PERANAKAN ETTAWA (PE) - Siti Badriyah, Siswanto, Erwanto, dan Arif Qisthon (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
This research aims to study the effect of microclimate manipulation on glucose levels and blood urea of boer goat and ettawa goat grade. This study was conducted on August—September 2018 in the UPTD Breeding Center of Negeri Sakti, the District of Pesawaran, Lampung. Analyzed of glucose levels and blood urea were done in UPTD Laboratorium Health Center of Bandar Lampung. This study used split plot design with treatments and 3 replications. The treatment in the research are the main plot is a cage without misting (K0) and a misting enclosure (K1). While the subplots are ettawa goat grade and Boer goats (T2).The data obtained were analyzed by variance analyzed with significant level of 5%. The results showed that the treatment of cage climate manipulation had no significant effect (P> 0,05) on glucose and urea in the blood. The conclusion is the climate manipulation cage, not influence with glucose and urea the blood. Keywords: Blood urea, Boer Goat, Ettawa goat grade, Glucose levels, Pen, Temperature